Analysis Of Epuskesmas Adoption In Tasikmalaya Regency Using Utaut Model - Ramadhani, Fauzia; Noviaristanti, Siska (PT. Publikasiku Academic Solution, 2024)
The 4.0 Revolution has rendered information technology an indispensable necessity in human life. Technological progress, particularly in healthcare, offers significant conveniences. The healthcare sector's technological evolution is marked by the digital transformation of Community Health Center (Puskesmas) information systems, with ePuskesmas becoming one such system. ePuskesmas serves as an online and integrated Puskesmas information system following the standards set by the Ministry of Health of the Republic of Indonesia through the Puskesmas Information System (SIP). Despite not being universally implemented, particularly in Tasikmalaya District, this study uses the UTAUT model. Variables include Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Behavioral Intention, and Use Behavior. This study uses a quantitative method by distributing online questionnaires to ePuskesmas users in 40 Puskesmas in Tasikmalaya District. All collected data met validity and reliability criteria and were assessed using SmartPLS 4.0 software. Hypotheses were tested using Partial Least Square Structural Equation Modeling (PLS-SEM), revealing that Performance Expectancy and Effort Expectancy significantly and positively influence Behavioral Intention. Behavioral Intention and Facilitating Conditions significantly and positively impact the Use Behavior of ePuskesmas.